KEUNGGULAN BERSAING MELALUI ORIENTASI PASAR DAN INOVASI PRODUK - Muhammad Bukhori Dalimunthe (Universitas Medan Area, 2017)
The aim of this study is to analyze the competitive advantage of the group of culinary business through market orientation and product innovation. This study conducted at group of culinary business in Suka Maju Village, District of West Binjai, Binjai. 76 responses was collected using a closed questionnaire containing the respondents perception of market orientation, innovation, and competitive advantage with purposive sampling technique. Furthermore, the data was analysed using path analysis. The results show; (1) Market orientation have direct and positive impact on innovation of product; (2) Market orientation have direct and positive impact on competitive advantage; (3) Innovation have direct and positive impact on competitive advantage; and (4) Innovation can increase the effect of market orientation on competitive advantage.Keywords: competitive advantage, market orientation, product innovation.